“Dribbling” the hegemonic media: alternative press in the propagation of women’s soccer (Intercom - Brazilian Journal of Communication Sciences, 2022)
This paper analyzes how alternative digital media proposes new ways of processing information and allows greater visibility to marginalized topics by the hegemonic press, rearranging meanings with mass media and consumers. The research is centered on women’s soccer, a subject that has historically received little attention from traditional Brazilian sports journalism, and its object study is the Dibradoras, a blog created in 2015 by a group of women whose aim is to expose gender inequalities in sports. The corpus is composed of 696 units published by Dibradoras on Twitter, between June 7 and July 7 of 2019, coinciding with the beginning and end of the Women’s World Cup in France. As a result, it is possible to suggest the empowering of an alternative media channel which amplifies the voice of the participants and promotes counter-hegemonic forms of visibility in women’s soccer.
Keywords: Alternative press; Social media; Gender; Women’s soccer; Case study